Letter from James Curtis Booth to H. S. Cochran - Booth, James Curtis (1881)
James Curtis Booth (1810-1888) writes to H.S. Cochran to request he construct a balance to "weigh gold and silver with the exactness which their value demands."
Keywords: Booth, James Curtis, 1810-1888; Scales (Weighing instruments); United States Mint; Mint of the United States